2020
DOI: 10.1021/acsomega.0c03284
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Solvent Influence on the Lipase-Catalyzed 1,3-Diolein Synthesis

Abstract: 1,3-Diacylglycerol preparation has roused increasing attention in recent years as the 1,3-diacylglycerol-rich oils can suppress the deposition of visceral fat and prevent the body weight increasing. Lipozyme TL IM-mediated esterification of oleic acid with monoolein was effective for 1,3-diacylglycerol production. During the esterification process, the solvent shows obvious influence on the diolein synthesis as well as the 1,3-diolein production. This work investigated the related kinetics and mechanism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…The flexibilities of FA-HY1 in different systems were also measured with RMSF, which could be used as a parameter reflecting the structure and function of enzymes. , Figure b illustrates the calculation of RMSF values by using trajectory data, followed by the convergence of the RMSD values of several systems. It is important to notice that the majority of RMSF values are under 1 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The flexibilities of FA-HY1 in different systems were also measured with RMSF, which could be used as a parameter reflecting the structure and function of enzymes. , Figure b illustrates the calculation of RMSF values by using trajectory data, followed by the convergence of the RMSD values of several systems. It is important to notice that the majority of RMSF values are under 1 Å.…”
Section: Resultsmentioning
confidence: 99%
“…They can change the configuration of enzymes in active site and lipase lid, respectively. (Huang et al, 2022a(Huang et al, , 2022cZitian et al, 2020). Although Novozym 435 is a lipase that acts as non-1,3 specific, when a great excess of ethanol is used, this lipase acts as 1,3-specific (Muñío et al, 2009).…”
Section: Sn-2 Fatty Acid Compositionmentioning
confidence: 99%
“…It was reported that in many cases lipases expressed higher catalytic activity but lower sn-1,3 selectivity with increasing log P of the solvents [89][90][91]. Bi et al [90] found that Candida sp.…”
Section: Solvent and Water Activitymentioning
confidence: 99%
“…Duan et al [89] observed the similar phenomenon when using Novozym 435 as the biocatalyst. The solvent effect on the regioselectivity was thought to be attributed to the variation of binding energy between lipase and different positions of hydroxyl groups [89][90][91]. On the contrary, whole-cell lipase from Aspergillus niger GZUF36 was found to exhibit stronger sn-1,3 selectivity in the solvent with higher log P value [92].…”
Section: Solvent and Water Activitymentioning
confidence: 99%
See 1 more Smart Citation